The Effect Of Livelihood Capital On Livelihood Resilience Of Sub-Urban Farming Households In Karangmukti Village, Bungursari District, Purwakarta Regency - Resa Ramadhan; Fatimah Azzahra; Syifa Fauziah (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2026)
Karangmukti Village in Bungursari District has experienced agricultural land conversion. Before the change, the agricultural land area was about 206 hectares. In 2025, approximately 30 hectares were converted, reducing the remaining agricultural land to 176 hectares. Most of this conversion was used for industrial and residential development. Furthermore, additional land conversion is planned for 2026–2027 to support the construction of new companies and housing areas, which may further decrease the amount of productive agricultural land in Karangmukti Village. This study aims to analyze the level of livelihood capital, the level of livelihood resilience, and the influence of livelihood capital on the livelihood resilience of farming households. The research applied a quantitative approach. Samples of farming households were determined using the Slovin formula and cluster sampling technique. Data were collected through questionnaires, interviews, observation, and documentation, and analyzed using quantitative descriptive analysis and Smart-PLS. The results indicate that the level of livelihood capital among farming households is moderate, with natural capital as the most dominant component. Livelihood resilience is also categorized as moderate. Further analysis shows that livelihood capital has a positive and significant influence on the livelihood resilience of farming households.